2018
DOI: 10.1128/jcm.01562-17
|View full text |Cite
|
Sign up to set email alerts
|

mcr-3 and mcr-4 Variants in Carbapenemase-Producing Clinical Enterobacteriaceae Do Not Confer Phenotypic Polymyxin Resistance

Abstract: Citation Teo JWP, Kalisvar M, Venkatachalam I, Ng OT, Lin RTP, Octavia S. 2018. mcr-3 and mcr-4 variants in carbapenemase-producing clinical Enterobacteriaceae do not confer phenotypic polymyxin resistance. J Clin Microbiol 56:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
34
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 12 publications
4
34
0
1
Order By: Relevance
“…CP000447), and mcr-4.3 showed 100% nucleotide identity to the sequence in the genome. These data supported the conclusion that mcr-4 and its alleles originated from Shewanella frigidimarina (6), while the identification of mcr-4.3 in A. baumannii resonated with the indication of horizontal gene transfer of mcr-4.3, according to the other two reports (14,15).…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…CP000447), and mcr-4.3 showed 100% nucleotide identity to the sequence in the genome. These data supported the conclusion that mcr-4 and its alleles originated from Shewanella frigidimarina (6), while the identification of mcr-4.3 in A. baumannii resonated with the indication of horizontal gene transfer of mcr-4.3, according to the other two reports (14,15).…”
Section: Resultssupporting
confidence: 80%
“…We could not determine whether transfer of pAB18PR065 could confer resistance to colistin. According to the other two studies, mcr-4.3 alone did not confer phenotypic resistance to colistin (14) and showed a lack of lipid A modification function (15). Recently, a study on the action and mechanism of MCR-4 showed that revertants of mcr-4.3 (either V179G or V236F) led to its expression and conferred colistin resistance of 8 g/ml, together with the acquired function of lipid A modification (22).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this finding, the entire coding sequence of mcr-4.3 cloned with its native promoter into plasmid pET-28a (ϩ) in E. coli DH10B cells also had a colistin MIC of 0.5 g/ml. Our results are in agreement with those of Teo et al (15), which show that the mcr-4.3 gene does not confer resistance to colistin. In contrast, in the original mcr-4.1 study, plasmid pMCR_R3445 was transformed into DH5␣ E. coli and had an MIC of 2 g/ml for colistin, which is an 8-fold increase compared with the MIC of the DH5␣ E. coli host (MIC, 0.25 g/ml) (9).…”
supporting
confidence: 94%
“…However, polymyxin use in animals and humans has promoted the selection and spread of mcr-1 drug-resistant strains . Since mcr-1 was discovered in food, animal and human isolates from Southern China, it has already spread to over 40 countries, implying that it played a prevalent role in the transferability of polymyxin resistance (Teo et al, 2017;Liu et al, 2016). In addition, mcr-1 positive plasmids could coexist with other resistance genes, notably ESBL genes; this has probably led to the emergence of pan-drug resistant strains and treatment failure (Haenni et al, 2016).…”
Section: Introductionmentioning
confidence: 99%